Separate Neural Systems Value Prosocial Behaviors and Reward: An ALE Meta-Analysis - Wang, Haixia; Zhang, Jian; Jia, Huiyuan (Frontiers in Human Neuroscience, 2019)
Background: It has been argued that prosocial behaviors and momentary rewards activate the similar reward systems. However, a recent theoretical hypothesis encourages a fundamentally different view. Specifically, the social heuristic hypothesis posits that individuals internalize prosocial behaviors that are advantageous in their daily social life. These advantageous behaviors are fundamentally different from tangible and immediate reward. Objectives: Our objectives are to test a hypothesis that these advantageous prosocial behaviors are so critical to survival that it is necessary to have a neural system in the brain that leads people to maintain repeated social interactions. These neural systems are different from the computations of rewards because prosocial behaviors are not advantageous if only considering the computations of rewards. Methods: To deepen the understanding of the neural systems of prosocial behaviors and reward, we conducted activation likelihood estimation (ALE) to examine brain activation in prosocial behaviors and reward tasks. Results: Prosocial behaviors specifically activated distinct brain systems to a greater degree than reward. These systems were implicated in the processing of social behaviors and included the insula, temporal lobe and superior temporal gyrus. By contrast, reward specifically activated the lentiform nucleus, thalamus, caudate nucleus, parahippocampal gyrus, and anterior cingulate cortex, which are associated with the brain reward system. Conclusions: These findings suggest that prosocial behaviors are different from reward and involve specific brain mechanisms.